KONSEP INNER BEAUTY; KAJIAN PENDIDIKAN AKHLAQ - M. Mukhlis Fahruddin (el-hikmah, 2012)
The concept of inner beauty in Islam refers to the appeal that radiates from within a person. The radiance of the inner beauty is reflected in moral quality, in managing one-self, in self-control, and in wisdom while dealing with life problems. This is the truest concept of inner beauty. However, it differs in common practice, for people prefer to pursue physical form of beauty, and dismiss the true beauty of personality and morality. This paper would like to remind the importance of moral education and provide new understanding of the concept of beauty within ourselves and that the development of inner beauty comes from the molding of dignifying morality, not out of polishing the physical appearance, but of refinement of behavior.